2019
DOI: 10.1016/j.isci.2019.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Molecule Discovery via C2-Substituent Promoted Oxidative Coupling of Indole and Enolate

Abstract: C2, C3-disubstituted indole is one of the most frequently encountered motifs in bioactive alkaloids and medicinal chemistry. Thus, developing novel, concise, and efficient access to it is highly desired in drug discovery. Herein, we present such an approach to this scaffold by direct oxidative coupling of C2-substituted indoles and enolates. Compared with indole bearing no C2-substituent, higher yields (up to 96%) were obtained for C2-substituted indoles in most cases. Mechanistic studies showed the reaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…The issues of toxic side effect and multidrug resistance (MDR) remain a challenge in the treatment and clinical management of NSCLC recently [31]. It is crucial to find some small molecules with good therapeutic potentials and low toxicity to act as a novel drug candidate for comprehensive treatment of NSCLC [24]. Repurposing old drugs in treating other diseases is a technique with many advantages including time and cost savings, since the safety and toxicity of candidate drugs have already been clearly studied [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The issues of toxic side effect and multidrug resistance (MDR) remain a challenge in the treatment and clinical management of NSCLC recently [31]. It is crucial to find some small molecules with good therapeutic potentials and low toxicity to act as a novel drug candidate for comprehensive treatment of NSCLC [24]. Repurposing old drugs in treating other diseases is a technique with many advantages including time and cost savings, since the safety and toxicity of candidate drugs have already been clearly studied [17].…”
Section: Discussionmentioning
confidence: 99%
“…2C showed that ISP-I treatment for 48h obviously ascended the abundance of cells in G2/M phase. The transition from G2 phase to mitosis was initiated by activated cyclin B1/cdc2 complex, which could be inhibited by the increased p21 [24,25]. As shown in Fig.…”
Section: Isp-i Induced Apoptosis and G2/m Arrest In Nsclc Cellsmentioning
confidence: 93%
“…The following section focus on summarizing the recent advances (2018–2021) made towards synthesis of indole core in the design of anti-cancer compounds that may act via various targets such as topoisomerase, tubulin, aromatase, kinases, etc. The review also discusses the SAR of potential lead accountable for anticancer activity 31 .…”
Section: Indole As Anticancer Drugsmentioning
confidence: 99%
“…Since both indole and benzo–furanone structural fragments are omnipresent in nature and listed as privileged scaffolds for drug discovery, chimeric indigo-, or isoindigo-like molecules possessing both these moieties also attracted certain attention. There are several reports describing the preparation of these unique compounds and studies of their applications in medicinal chemistry and material sciences [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. A common theme described in these reports is the metal-catalyzed C-C bond-forming reactions to accomplish the coupling between the indole and benzofuranone building blocks [ 1 , 5 , 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports describing the preparation of these unique compounds and studies of their applications in medicinal chemistry and material sciences [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. A common theme described in these reports is the metal-catalyzed C-C bond-forming reactions to accomplish the coupling between the indole and benzofuranone building blocks [ 1 , 5 , 8 , 10 ]. Other approaches used a Lewis acid-mediated reaction of indole derivatives with properly functionalized aromatic precursors (typically phenols or quinones) to furnish a five-membered lactone cycle in benzofurane [ 2 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%